OPTIMIZATION OF SURFACE TREATMENT AND FUNCTIONALIZATION OF MULTIWALLED CARBON NANOTUBES (MWCNT) FOR CARBON DIOXIDE (C02) ADSORPTION - RAHMAM, SYUHAIDAH (2014)
The unique characteristics of multiwalled carbon nanotubes (MWCNT) such as high porosity, high surface area and the existence of surface functional groups through chemical modification makes it a suitable material for adsorption of carbon dioxide (CO2). However, due to its hydrophobicity and the bundling issues, MWCNT could not function as an effective adsorbent. Thus treatment on MWCNT is required to overcome these problems before it could be functionalized with the amine group that will assist MWCNT adsorbing C02. The objective of the work is to optimize the surface treatment and functionalization of MWCNT with 3-Aminopropyl triethoxysilane (APTS) for enhanced adsorption of carbon dioxide. Three types of acids were used for surface treatment namely sulfuric acid (H2SO4), nitric acid (HNO3), and the mixture of sulfuric and nitric acid (HNO3/H2SO4).